Proteoglycan remodeling is accelerated in women with angina pectoris and diffuse myocardial fibrosis: the iPOWER Study. (25th November 2020) - Mygind, N.D; Holm Nielsen, S; Mide Michelsen, M; Pena, A; Bechsgaard Frestad, D; Suhrs, E; Bove, K.B; Genovese, F; Nielsen, H.B; Karsdal, M; Vejlstrup, N; Prescott, E; et al.
Abstract: Background: Women with angina and no obstructive coronary artery disease (CAD) have an unfavourable prognosis, possibly due to coronary microvascular disease and diffuse myocardial fibrosis (DMF). In DMF myocardial extracellular matrix (ECM) proteins are actively remodeled by matrix metalloproteinase (MMP). Purpose: We investigated MMP-mediated degradation of the protegoglycans biglycan and versican in women with angina pectoris and possible DMF assessed by cardiac magnetic resonance T1 mapping. Methods: Seventy-one women with angina pectoris and no obstructive CAD were included. Asymptomatic age-matched women served as controls (n=32). Versican and biglycan were measured in serum by specific competitive enzyme-linked immunosorbent assays. T1 mapping was performed by cardiac magnetic resonance with gadolinium measuring T1 and extracellular volume (ECV). Results: Both biglycan and versican levels were higher in symptomatic women compared with controls; 31.4 ng/mL vs. 16.4 ng/mL (p<0.001) and 2.1 ng/mL vs. 1.8 ng/mL (p<0.001), respectively (Figure 1) and were moderately correlated to global ECV (r2=0.38, p<0.001 and r2=0.26, p=0.015 respectively). Conclusion: Turnover of biglycan and versican was increased in symptomatic compared to asymptomatic women and associated to ECV, supporting a link between angina with no obstructive CAD and fibrotic cardiac remodeling. The examined biomarkers may prove to be suitable for monitoring active ECM remodeling. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): This work was supported by The Danish Heart Foundation, the Danish Research Fund (Den Danske Forskningsfond) and by University of Copenhagen.